(untitled) (Global Journal of Science Frontier Research, 2020)
There is overwhelming evidence on the robust relationship between housing and health, and the effect of poor housing conditions on health risks and outcomes. Although adequate housing is a fundamental human right and an essential social determinant of health, global prevalence of poor housing conditions is a key public health issue. Identification of the factors of housing associated with health and wellbeing, and investigation of health risks and outcomes attributed to housing conditions are essential preventive measures to ensure enhancement of both housing conditions and overall health. On the other hand, demographic changes and current trends of population growth indicate increased pressure on housing and health sectors globally. Current demographic trends suggest rapid growth of ageing population and increased urbanisation as the major challenges.